L'exili català a Cambridge. A propòsit de la Jornada commemorativa del 50é aniversari de l'AILLC. - GARCIA-OLIVER, BLANCA (Scripta)
This work is a journey through the trajectory of the Associació de Llengua i Liteeratura Catalanes (AILLC), since its founding, 50 years ago. He also mentioned in his review of the events that will be held in Cambridge, in order to remember that anniversary.